Ultrahigh-nickel ternary single-crystal positive electrode material and preparation method thereof

By coating the ultra-high nickel ternary single crystal positive electrode material with halide solid electrolyte, carbon source and carbon paper, the problem of insufficient contact between the positive electrode material and the electrolyte in the solid-state battery is solved, and the electrochemical performance and cycle stability of the material are improved.

CN120709324APending Publication Date: 2025-09-26GEM WUXI ENERGY MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510860748.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Existing ultra-high nickel ternary single crystal positive electrode materials have poor electrochemical performance in solid-state batteries, especially insufficient contact between the positive electrode material and the solid electrolyte and difficulty in ion transmission, which leads to decreased battery performance.

Method used

The ultra-high nickel ternary single crystal positive electrode material is coated with a halide solid electrolyte, a carbon source and carbon paper to form a fiber network to improve the electrical conductivity, and the halide solid electrolyte is used as a fast ion conductor coating layer to enhance the ion transfer rate and interface contact of the material.

Benefits of technology

The electrical and electrochemical properties of the positive electrode material are improved, the lithium ion conductivity is enhanced, the high conductive phase is stabilized, the operating temperature range is broadened, and the cycle life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of positive electrode materials, in particular to an ultrahigh-nickel ternary single-crystal positive electrode material and a preparation method thereof. The invention provides an ultrahigh-nickel ternary single-crystal positive electrode material. The positive electrode material is obtained by coating halide solid electrolyte, a carbon source and carbon paper. The halide solid electrolyte, the carbon source and the carbon paper are used for coating the ultrahigh-nickel ternary single-crystal positive electrode material, on one hand, the positive electrode material is formed by using a fiber network of the carbon paper to improve the electrochemical performance of the positive electrode material, and on the other hand, the positive electrode material and the solid electrolyte are effectively isolated by using the carbon source and the carbon paper to reduce interface side reactions and improve the electrochemical performance of the positive electrode material. Meanwhile, the halide solid electrolyte is adopted as a fast ion conductor coating layer, so that the ion transmission rate of the positive electrode material can be increased, the problem of insufficient contact between the positive electrode material of the solid-state battery and the solid electrolyte can be solved, and the electrical performance and the electrochemical performance of the positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to an ultra-high nickel ternary single crystal positive electrode material and a preparation method thereof. Background Art

[0002] Ternary lithium-ion batteries are considered the mainstay and future of automotive batteries due to their excellent energy density. High-nickel, low-cobalt ternary cathode materials have become one of the main development directions for ternary cathode materials due to their high theoretical specific capacity, and are currently one of the main development directions for solid-state battery cathode materials. However, when the Ni content in layered ultra-high nickel cathode materials is increased, structural instability is caused by the shrinkage of the anisotropic lattices under deep charging conditions, resulting in local stress concentration along the particle boundaries and developing into microcracks, leading to serious side reactions and even particle pulverization. Studies have found that single-crystal cathode materials have many advantages that secondary spherical particles do not have, including high mechanical strength, high compaction density, and resistance to crushing; there is little intergranular cracking caused by anisotropic expansion; and the advantages of a smooth surface and minimal interfacial side reactions.

[0003] Although ultra-high nickel single crystal materials have significant advantages, there are still several technical bottlenecks. First, the primary grain size of single crystal materials is significantly larger than that of polycrystalline materials, which leads to a decrease in the kinetic rate of lithium ionization during calcination. Second, high nickel content can easily cause Ni 3+ Decomposition, and then produce surface residual alkali, which will not only cause the gelation of the positive electrode slurry (leading to increased difficulty in the coating process), but also destroy the surface lattice structure, and ultimately affect the capacity characteristics and cycle stability of the material. Compared with the liquid electrolyte system, the solid-solid contact between the solid electrolyte and the positive electrode material has problems such as limited interface contact area and blocked ion transmission path. In particular, sulfide solid electrolytes are prone to violent interfacial side reactions with high-nickel positive electrode materials, which may cause electrolyte decomposition and accompanied by gas production, seriously affecting battery performance. These key issues urgently need to be solved through means such as interface engineering and material modification. At present, the modification method of coating is usually used to effectively reduce the problem of residual alkali, thereby improving the cycle stability of the material.

[0004] Existing technologies usually use materials such as metal oxides or phosphates for coating. Although this can improve the electrical properties of the positive electrode material to a certain extent, when applied to solid-state batteries, there are often problems such as insufficient contact between the positive electrode material and the solid electrolyte, and difficulty in ion transmission, which affects the electrochemical performance of the positive electrode material. Summary of the Invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defect of poor electrochemical performance of the positive electrode materials used in solid-state batteries in the prior art, thereby providing an ultra-high nickel ternary single crystal positive electrode material and a preparation method thereof.

[0006] To this end, on the one hand, the present invention provides an ultra-high nickel ternary single crystal positive electrode material, which is obtained by coating a halide solid electrolyte, a carbon source and carbon paper.

[0007] In some embodiments, the chemical formula of the halide solid electrolyte is Li3MX6, wherein M includes at least one of In, Y, Sc, and Er, and X includes at least one of F, Cl, and Br.

[0008] In some embodiments, the thickness of the carbon paper is 0.18-0.22 mm, and the surface density of the carbon paper is 70-90 g / m 2 .

[0009] In some embodiments, the carbon source includes at least one of carbon black, carbon powder, graphite powder or glucose.

[0010] In some embodiments, the carbon paper is free of a hydrophobic coating.

[0011] In some embodiments, the content of the carbon paper is 5-15 wt % based on the total weight of the ultra-high nickel ternary single crystal positive electrode material.

[0012] In some of the embodiments, the content of the halide solid electrolyte is 0.5-2 wt % based on the total weight of the ultra-high nickel ternary single crystal positive electrode material.

[0013] In some of the embodiments, the content of the carbon source is 0.2-1 wt % based on the total weight of the ultra-high nickel ternary single crystal positive electrode material.

[0014] In some embodiments, the ultra-high nickel ternary single crystal positive electrode material also includes a doping material, the doping material includes a metal element or a phosphate, and the metal element includes at least one of aluminum, magnesium, titanium, vanadium, gallium, yttrium, zirconium, niobium, molybdenum, antimony, tantalum, tungsten, and cobalt.

[0015] On the other hand, the present invention provides a method for preparing the above-mentioned ultra-high nickel ternary single crystal positive electrode material, comprising the following steps: mixing an ultra-high nickel metal precursor, a halide solid electrolyte and a carbon source to form a mixture, placing the mixture on carbon paper, and sintering it in an inert atmosphere to obtain an ultra-high nickel ternary single crystal positive electrode material.

[0016] In some embodiments, the sintering temperature is 400-600° C., and the sintering time is 4-10 h.

[0017] In some embodiments, the inert atmosphere includes at least one of nitrogen, argon, or helium.

[0018] In some embodiments, the preparation method of the ultra-high nickel metal precursor includes the following steps: S1, mixing a nickel-cobalt-manganese precursor, a lithium source and a first additive, and sintering to obtain a sintered material; S2, mixing a sintered material, a lithium source and a second additive, and sintering to obtain an ultra-high nickel positive electrode material.

[0019] In some embodiments, in step S1, the chemical formula of the nickel-cobalt-manganese precursor is Ni a Co b Mn c (OH)2, wherein a≥0.9, 0.02≤b≤0.06, 0.01≤c≤0.03, a+b+c=1.

[0020] In some embodiments, the first additive includes a metal oxide, and the metal oxide includes at least one of magnesium oxide, aluminum oxide, titanium oxide, vanadium oxide, gallium oxide, strontium oxide, yttrium oxide, zirconium oxide, niobium oxide, molybdenum oxide, antimony oxide, lanthanum oxide, tantalum oxide, and tungsten oxide.

[0021] In some embodiments, in step S2, the second additive includes a cobalt source, an aluminum source and a phosphate, the cobalt source includes at least one of cobaltous hydroxide, cobalt oxyhydroxide, and cobalt oxide, the aluminum source includes at least one of aluminum hydroxide or aluminum oxide, and the phosphate includes at least one of diammonium hydrogen phosphate and ammonium dihydrogen phosphate.

[0022] In some embodiments, the sintering temperature in step S1 is 600-900° C., preferably 700-800° C., the sintering time is 6-20 h, and the sintering atmosphere is oxygen.

[0023] In some embodiments, in step S1, based on the mass of the nickel-cobalt-manganese precursor, the content of the first additive is 0.05-1.5 wt %, and the molar ratio of the lithium source to the nickel-cobalt-manganese precursor is 1-1.04:1.

[0024] In some embodiments, in step S2, the sintering temperature is 500-700° C., the sintering time is 4-10 h, and the sintering atmosphere is oxygen.

[0025] In some embodiments, in step S2, based on the mass of the sintered material, the content of the lithium source is 0.1-0.5 wt %, and the content of the second additive is 0.001 wt % to 0.9 wt %.

[0026] The technical solution of the present invention has the following advantages:

[0027] 1. The present invention provides an ultra-high nickel ternary single crystal positive electrode material, which is coated with a halide solid electrolyte, a carbon source, and carbon paper. The present invention uses a halide solid electrolyte, a carbon source, and carbon paper to coat the ultra-high nickel ternary single crystal positive electrode material. On the one hand, the fiber network of the carbon paper is used to form the positive electrode material, thereby improving the electrochemical performance of the positive electrode material. On the other hand, the carbon source and carbon paper are used to effectively isolate the positive electrode material and the solid electrolyte, thereby reducing interfacial side reactions and improving electrical conductivity. At the same time, the halide solid electrolyte is used as a fast ion conductor coating layer, which not only increases the ion transfer rate of the positive electrode material, but also solves the problem of insufficient contact between the positive electrode material and the solid electrolyte of the solid-state battery, thereby improving the electrical and electrochemical properties of the positive electrode material.

[0028] 2. The present invention provides an ultra-high nickel ternary single crystal cathode material. The halide solid electrolyte has the chemical formula Li3MX6, where M comprises at least one of In, Y, Sc, and Er, and X comprises at least one of F, Cl, and Br. This material utilizes F, Cl, and Br as halogens and In, Y, Sc, and Er as metal elements. By combining halogens and metal elements to manipulate the lattice structure and introduce controllable disorder, the material significantly improves lithium-ion conductivity, stabilizes the highly conductive phase, and broadens the operating temperature range. It also enhances electrochemical stability, particularly compatibility with high-voltage cathodes, and strengthens structural stability, extending cycle life.

[0029] 3. The present invention provides an ultra-high nickel ternary single crystal cathode material. This material is prepared by mixing an ultra-high nickel metal precursor, a halide solid electrolyte, and a carbon source to form a mixture. The mixture is then placed on carbon paper and sintered in an inert atmosphere to produce the ultra-high nickel ternary single crystal cathode material. The preparation method provided by the present invention is simple, and the resulting cathode material offers stable chemical properties and a long cycle life.

[0030] 4. The present invention provides an ultra-high nickel ternary single crystal cathode material. The method for preparing the ultra-high nickel metal precursor comprises the following steps: S1. Mixing a nickel-cobalt-manganese precursor, a lithium source, and a first additive, and sintering to obtain a sintered material; S2. Mixing the sintered material, a lithium source, and a second additive, and sintering to obtain the ultra-high nickel cathode material. The present invention utilizes two additive additions: the first additive is bulk doping, which can produce a more stable result; the second additive is surface coating, which reduces electrolyte corrosion. DETAILED DESCRIPTION

[0031] The following examples are provided for a better understanding of the present invention and are not intended to limit the best mode of implementation. They do not limit the content and scope of protection of the present invention. Any product identical or similar to the present invention obtained by anyone under the guidance of the present invention or by combining the features of the present invention with other prior arts shall fall within the scope of protection of the present invention.

[0032] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in this field can be used. If the manufacturer of the reagents or instruments is not specified, they are all commercially available conventional reagents.

[0033] Example 1

[0034] This embodiment provides a method for preparing an ultra-high nickel ternary single crystal positive electrode material. The specific steps and parameters are as follows:

[0035] (1) 600g of Ni with an average particle size of 2.5μm 0.93 Co 0.05 Mn 0.02 (OH)2 ternary precursor, 275.16g lithium hydroxide monohydrate, 1.043g magnesium oxide, and 0.850g zirconium oxide were mixed in a high-speed mixer until there were no white spots, placed in a muffle furnace, and sintered at 780°C in an oxygen atmosphere for 10 hours. After that, the sintered material was crushed, pulverized, and sieved.

[0036] (2) 600 g of the first sintered material obtained in step (1), 1.8 g of lithium hydroxide monohydrate, 3 g of cobaltous hydroxide, and 3 g of γ-alumina were mixed in a high-speed mixer, placed in a muffle furnace, and sintered at 600° C. in an oxygen atmosphere for 6 h. The second sintered material was then crushed and sieved.

[0037] (3) 500g of the second burnt material obtained in step (2), 2.5g of glucose and 5g of Li3InCl6 were mixed in a high-speed mixer and evenly applied on a 50g, 0.20mm thick, 80g / m2 surface density plate. 2 The positive electrode sheet was obtained by pressing and cutting with a mold of corresponding size using a 13kN pressing roller on a carbon paper without hydrophobic coating, placing it in a muffle furnace, sintering it at 500°C in a nitrogen atmosphere for 6 hours.

[0038] Example 2

[0039] (1) 600g of Ni with an average particle size of 2.5μm 0.93 Co 0.05 Mn 0.02 (OH)2 ternary precursor, 275.16g lithium hydroxide monohydrate, 1.043g magnesium oxide, and 0.850g zirconium oxide were mixed in a high-speed mixer until there were no white spots, placed in a muffle furnace, and sintered at 780°C in an oxygen atmosphere for 10 hours. After that, the sintered material was crushed, pulverized, and sieved.

[0040] (2) 600 g of the first sintered material obtained in step (1), 1.8 g of lithium hydroxide monohydrate, 3 g of cobaltous hydroxide, and 3 g of γ-alumina were mixed in a high-speed mixer, placed in a muffle furnace, and sintered at 600° C. in an oxygen atmosphere for 6 h. The second sintered material was then crushed and sieved.

[0041] (3) After 500g of the second burnt material obtained in step (2), 2.5g of glucose and 5g of LiYCl were mixed in a high-speed mixer, the mixture was evenly spread on a 50g, 0.20mm thick, 80g / m2 surface density plate. 2 The positive electrode sheet was obtained by pressing and cutting with a mold of corresponding size using a 13kN pressing roller on a carbon paper without hydrophobic coating, placing it in a muffle furnace, sintering it at 500°C in a nitrogen atmosphere for 6 hours.

[0042] Example 3

[0043] (1) 600g of Ni with an average particle size of 2.5μm 0.93 Co 0.05 Mn 0.02 (OH)2 ternary precursor, 275.16g lithium hydroxide monohydrate, 1.043g magnesium oxide, and 0.850g zirconium oxide were mixed in a high-speed mixer until there were no white spots, placed in a muffle furnace, and sintered at 780°C in an oxygen atmosphere for 10 hours. After that, the sintered material was crushed, pulverized, and sieved.

[0044] (2) 600 g of the first sintered material obtained in step (1), 1.8 g of lithium hydroxide monohydrate, 3 g of cobaltous hydroxide, and 3 g of γ-alumina were mixed in a high-speed mixer, placed in a muffle furnace, and sintered at 600° C. in an oxygen atmosphere for 6 h. The second sintered material was then crushed and sieved.

[0045] (3) 500g of the second burnt material obtained in step (2), 2.5g of glucose and 5g of Li3ScCl6 were mixed in a high-speed mixer and evenly applied on a 50g, 0.20mm thick, 80g / m2 surface density 2 The positive electrode sheet was obtained by pressing and cutting with a mold of corresponding size using a 13kN pressing roller on a carbon paper without hydrophobic coating, placing it in a muffle furnace, sintering it at 500°C in a nitrogen atmosphere for 6 hours.

[0046] Example 4

[0047] This embodiment provides a method for preparing an ultra-high nickel ternary single crystal positive electrode material. The specific steps and parameters are the same as those in Example 1, except that the thickness of the carbon paper without hydrophobic coating in step (3) is 0.18 mm.

[0048] Example 5

[0049] This embodiment provides a method for preparing an ultra-high nickel ternary single crystal positive electrode material. The specific steps and parameters are the same as those in Example 1, except that the thickness of the carbon paper without hydrophobic coating in step (3) is 0.19 mm.

[0050] Example 6

[0051] This embodiment provides a method for preparing an ultra-high nickel ternary single crystal positive electrode material. The specific steps and parameters are the same as those in Example 1, except that the surface density of the carbon paper without hydrophobic coating in step (3) is 50 g / m 2 .

[0052] Example 7

[0053] This embodiment provides a method for preparing an ultra-high nickel ternary single crystal positive electrode material. The specific steps and parameters are the same as those in Example 1, except that the surface density of the carbon paper without hydrophobic coating in step (3) is 60 g / m 2 .

[0054] Example 8

[0055] This embodiment provides a method for preparing an ultra-high nickel ternary single crystal positive electrode material. The specific steps and parameters are the same as those in Example 1, except that step (1) does not contain the first additive. The specific steps are as follows:

[0056] (1) 600g of Ni with an average particle size of 2.5μm 0.93 Co 0.05 Mn 0.02 The (OH)2 ternary precursor and 275.16 g of lithium hydroxide monohydrate were mixed in a high-speed mixer, placed in a muffle furnace, and sintered at 780°C in an oxygen atmosphere for 10 hours. The sintered material was then crushed, pulverized, and sieved.

[0057] (2) 600 g of the first sintered material obtained in step (1), 1.8 g of lithium hydroxide monohydrate, 3 g of cobaltous hydroxide, and 3 g of γ-alumina were mixed in a high-speed mixer, placed in a muffle furnace, and sintered at 600° C. in an oxygen atmosphere for 6 h. The second sintered material was then crushed and sieved.

[0058] (3) 500g of the second burnt material obtained in step (2), 2.5g of glucose and 5g of Li3InCl6 were mixed in a high-speed mixer and evenly applied on a 50g, 0.20mm thick, 80g / m2 surface density plate. 2 The positive electrode sheet was obtained by pressing and cutting with a mold of corresponding size using a 13kN pressing roller on a carbon paper without hydrophobic coating, placing it in a muffle furnace, sintering it at 500°C in a nitrogen atmosphere for 6 hours.

[0059] Example 9

[0060] This embodiment provides a method for preparing an ultra-high nickel ternary single crystal positive electrode material. The specific steps and parameters are the same as those in Example 1, except that the second additive is not contained.

[0061] (1) 600g of Ni with an average particle size of 2.5μm 0.93 Co 0.05 Mn 0.02 (OH)2 ternary precursor, 275.16g lithium hydroxide monohydrate, 1.043g magnesium oxide, and 0.850g zirconium oxide were mixed in a high-speed mixer, placed in a muffle furnace, and sintered at 780°C in an oxygen atmosphere for 10 hours. After that, a sintered material was obtained by crushing, grinding, and sieving.

[0062] (2) 600 g of the first sintered material obtained in step (1) was placed in a muffle furnace and sintered at 600° C. in an oxygen atmosphere for 6 h, and then crushed and sieved to obtain the second sintered material.

[0063] (3) 500g of the second burnt material obtained in step (2), 2.5g of glucose and 5g of Li3InCl6 were mixed in a high-speed mixer and evenly applied on a 50g, 0.20mm thick, 80g / m2 surface density plate. 2 The positive electrode sheet was obtained by pressing and cutting with a mold of corresponding size using a 13kN pressing roller on a carbon paper without hydrophobic coating, placing it in a muffle furnace, sintering it at 500°C in a nitrogen atmosphere for 6 hours.

[0064] Example 10

[0065] This embodiment provides a method for preparing an ultra-high nickel ternary single crystal positive electrode material. The specific steps and parameters are as follows:

[0066] (1) Ni with an average particle size of 2.5 μm 0.93 Co 0.05 Mn 0.02 The (OH)2 ternary precursor, lithium hydroxide monohydrate, aluminum oxide and titanium oxide were mixed in a high-speed mixer, placed in a muffle furnace, and sintered at 780°C in an oxygen atmosphere for 10 hours. The mixture was then crushed, pulverized and sieved to obtain a sintered material, in which the ratio of the molar amount of lithium to the molar amount of nickel, cobalt and manganese elements was 1:1. Based on the mass of the ternary precursor, the aluminum oxide content was 0.02wt%, and the titanium oxide content was 0.03wt%.

[0067] (2) The first sintered material obtained in step (1), lithium hydroxide monohydrate, cobalt oxide, and aluminum hydroxide are mixed in a high-speed mixer, placed in a muffle furnace, and sintered at 600° C. in an oxygen atmosphere for 6 hours. The second sintered material is then crushed and sieved to obtain a second sintered material, wherein, based on the mass of the first sintered material, the content of lithium element is 0.2wt%, the content of cobalt oxide is 0.4wt%, and the content of aluminum hydroxide is 0.5wt%.

[0068] (3) 500g of the second sintered material obtained in step (2), 1g of graphite powder and 2.5g of Li3InCl6 were mixed in a high-speed mixer and evenly applied on a 75g, 0.20mm thick, 80g / m2 surface density sheet. 2 The positive electrode sheet was obtained by pressing and cutting with a mold of corresponding size using a 13kN pressing roller on a carbon paper without hydrophobic coating, placing it in a muffle furnace, sintering it at 500°C in a nitrogen atmosphere for 6 hours.

[0069] Example 11

[0070] This embodiment provides a method for preparing an ultra-high nickel ternary single crystal positive electrode material. The specific steps and parameters are as follows:

[0071] (1) Ni with an average particle size of 2.5 μm 0.93 Co 0.05 Mn 0.02 The (OH)2 ternary precursor, lithium hydroxide monohydrate, aluminum oxide and titanium oxide were mixed in a high-speed mixer, placed in a muffle furnace, and sintered at 780°C in an oxygen atmosphere for 10 hours. The mixture was then crushed, pulverized and sieved to obtain a sintered material, in which the ratio of the molar amount of lithium to the molar amount of nickel, cobalt and manganese elements was 1:1.04. Based on the mass of the ternary precursor, the aluminum oxide content was 0.5wt%, and the titanium oxide content was 1wt%.

[0072] (2) The first sintered material obtained in step (1), lithium hydroxide monohydrate, cobalt oxyhydroxide, and aluminum hydroxide are mixed in a high-speed mixer, placed in a muffle furnace, and sintered at 600° C. in an oxygen atmosphere for 6 hours. The second sintered material is then crushed and sieved to obtain a second sintered material, wherein, based on the mass of the first sintered material, the content of lithium element is 0.1wt%, the content of cobalt oxyhydroxide is 0.0005wt%, and the content of aluminum hydroxide is 0.0005wt%.

[0073] (3) After 500g of the second sintered material obtained in step (2), 5g of graphite powder and 10g of Li3InCl6 were mixed in a high-speed mixer, the mixture was evenly spread on a 25g, 0.20mm thick, 80g / m2 surface density sheet. 2 The positive electrode sheet was obtained by pressing and cutting with a mold of corresponding size using a 13kN pressing roller on a carbon paper without hydrophobic coating, placing it in a muffle furnace, sintering it at 500°C in a nitrogen atmosphere for 6 hours.

[0074] Comparative Example 1

[0075] This comparative example provides a method for preparing an ultra-high nickel ternary single crystal positive electrode material. The specific steps and parameters are the same as those in Example 1, except that step (3) does not contain Li3InCl6.

[0076] Comparative Example 2

[0077] This comparative example provides a method for preparing an ultra-high nickel ternary single crystal positive electrode material. The specific steps and parameters are the same as those in Example 1, except that step (3) does not contain glucose.

[0078] Comparative Example 3

[0079] This comparative example provides a method for preparing an ultra-high nickel ternary single crystal positive electrode material. The specific steps and parameters are the same as those in Example 1, except that step (3) does not contain carbon paper. That is, 500 g of the sintered material obtained in step (2), 2.5 g of glucose, and 5 g of Li3InCl6 are directly mixed in a high-speed mixer, placed in a muffle furnace, and sintered at 500°C in a nitrogen atmosphere for 6 h. After cooling, a 13 kN pressing roller is used and a mold of corresponding size is used to press and cut to obtain a positive electrode sheet.

[0080] Experimental example

[0081] The positive electrode sheets formed in Examples 1-11 and Comparative Examples 1-3 were respectively used to prepare lithium-ion solid-state mold batteries using the following method. The specific method is as follows:

[0082] In the argon atmosphere of the glove box, the lithium phosphorus sulfur chlorine solid electrolyte is evenly coated on the positive electrode sheet, wherein the lithium phosphorus sulfur chlorine solid electrolyte coating surface density is 45mg / cm 2 The cathode electrode sheet and solid electrolyte layer are formed using a roller press at 40 kN. The lithium metal sheet is used as the negative electrode sheet. The negative lithium metal sheet, solid electrolyte layer, and positive electrode sheet are assembled in this order in a battery case covered with an insulating sleeve and pressed into a battery.

[0083] Then, at 25°C, charge at a rate of 0.2C to 4.25V, and then discharge at a rate of 0.2C to 2.8V. This constitutes one cycle. The charge and discharge capacity at this time is the initial charge and discharge specific capacity, and the charge and discharge ratio is the initial efficiency. After two cycles, charge and discharge at 1C for 50 cycles. The charge and discharge capacity of the third cycle and the charge and discharge capacity of the 52nd cycle are recorded. The retention rate is the ratio of the discharge capacity of the 52nd cycle to the discharge capacity of the third cycle. The test results are shown in Table 1.

[0084] Table 1 Battery performance results

[0085]

[0086]

[0087] According to Table 1, compared with Comparative Examples 1-3, which are positive electrode materials formed without a halide solid electrolyte, without a carbon source, or without carbon paper, the present invention coats the positive electrode material with a halide solid electrolyte, a carbon source, and carbon paper in sequence, which not only improves the first-cycle and 1C discharge specific capacity and the first-cycle efficiency, but also improves the cycle retention rate of the positive electrode material.

[0088] Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the implementation methods. Those skilled in the art will readily appreciate that other variations or modifications based on the above descriptions are possible. It is not necessary and impossible to enumerate all implementation methods here. Obvious variations or modifications arising therefrom remain within the scope of protection of the present invention.

Claims

1. An ultra-high nickel ternary single crystal positive electrode material, characterized in that: The positive electrode material is obtained by coating a halide solid electrolyte, a carbon source and carbon paper.

2. The ultra-high nickel ternary single crystal positive electrode material according to claim 1, characterized in that: The chemical formula of the halide solid electrolyte is Li3MX6, wherein M includes at least one of In, Y, Sc, and Er, and X includes at least one of F, Cl, and Br.

3. The ultra-high nickel ternary single crystal positive electrode material according to claim 1, characterized in that: The thickness of the carbon paper is 0.18-0.22 mm, and the surface density of the carbon paper is 70-90 g / m 2 and / or, The carbon source includes at least one of carbon black, carbon powder, graphite powder or glucose.

4. The ultra-high nickel ternary single crystal positive electrode material according to claim 3, characterized in that: The carbon paper is carbon paper without a hydrophobic coating; and / or, The carbon paper content is 5-15 wt% based on the total weight of the ultra-high nickel ternary single crystal positive electrode material; and / or, The content of the halide solid electrolyte is 0.5-2 wt% based on the total weight of the ultra-high nickel ternary single crystal positive electrode material; and / or, Based on the total weight of the ultra-high nickel ternary single crystal positive electrode material, the content of the carbon source is 0.2-1wt%.

5. The ultra-high nickel ternary single crystal positive electrode material according to claim 1, characterized in that: The ultra-high nickel ternary single crystal positive electrode material also includes a doping material, which includes a metal element or a phosphate, and the metal element includes at least one of aluminum, magnesium, titanium, vanadium, gallium, yttrium, zirconium, niobium, molybdenum, antimony, tantalum, tungsten, and cobalt.

6. A method for preparing the ultra-high nickel ternary single crystal positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are included: An ultra-high nickel metal precursor, a halide solid electrolyte and a carbon source are mixed to form a mixture, the mixture is placed on carbon paper, and sintered in an inert atmosphere to obtain an ultra-high nickel ternary single crystal positive electrode material.

7. The preparation method according to claim 6, characterized in that The sintering temperature is 400-600°C and the sintering time is 4-10h; The inert atmosphere includes at least one of nitrogen, argon or helium.

8. The preparation method according to claim 6, characterized in that The method for preparing the ultra-high nickel metal precursor comprises the following steps: S1, mixing a nickel-cobalt-manganese precursor, a lithium source and a first additive, and sintering to obtain a sintered material; S2. Mixing the first sintered material, the lithium source and the second additive, and sintering to obtain an ultra-high nickel positive electrode material.

9. The preparation method according to claim 8, characterized in that In step S1, the chemical formula of the nickel-cobalt-manganese precursor is Ni a Co b Mn c (OH)2, wherein a≥0.9, 0.02≤b≤0.06, 0.01≤c≤0.03, a+b+c=1; and / or, The first additive includes a metal oxide, and the metal oxide includes at least one of magnesium oxide, aluminum oxide, titanium oxide, vanadium oxide, gallium oxide, strontium oxide, yttrium oxide, zirconium oxide, niobium oxide, molybdenum oxide, antimony oxide, lanthanum oxide, tantalum oxide, and tungsten oxide; and / or, In step S2, the second additive includes a cobalt source, an aluminum source and a phosphate, The cobalt source includes at least one of cobaltous hydroxide, cobalt oxyhydroxide, and cobalt oxide. The aluminum source includes at least one of aluminum hydroxide or aluminum oxide, The phosphate includes at least one of diammonium hydrogen phosphate and ammonium dihydrogen phosphate.

10. The preparation method according to claim 9, characterized in that In step S1, the sintering temperature is 600-900° C., preferably 700-800° C., the sintering time is 6-20 hours, and the sintering atmosphere is oxygen; and / or, In step S1, the content of the first additive is 0.05-1.5wt% based on the mass of the nickel-cobalt-manganese precursor. The molar ratio of the lithium source to the nickel-cobalt-manganese precursor is 1-1.04:1; and / or, In step S2, the sintering temperature is 500-700° C., the sintering time is 4-10 hours, and the sintering atmosphere is oxygen; and / or, In the step S2, the content of the lithium source is 0.1-0.5 wt % based on the mass of the sintered material. The content of the second additive is 0.001 wt% to 0.9 wt%.

Citation Information

Patent Citations

  • High-nickel ternary nickel cobalt lithium manganate positive electrode material and preparation method thereof

    CN113871613A

  • Positive electrode material with mixed conductor coating layer as well as preparation method and application of positive electrode material

    CN115050962A

  • Positive pole piece as well as preparation method and application thereof

    CN118553861A